Assessment of biological leaf tissue using biospeckle laser imaging technique. (9th May 2018) - Ansari, M Z; Mujeeb, A; Nirala, A K
Abstract: We report on the application of an optical imaging technique, the biospeckle laser, as a potential tool to assess biological and medicinal plant leaves. The biospeckle laser technique is a non-invasive and non-destructive optical technique used to investigate biological objects. Just after their removal from plants, the torn leaves were used for biospeckle laser imaging. Quantitative evaluation of the biospeckle data using the inertia moment (IM) of the time history speckle pattern, showed that the IM can be utilized to provide a biospeckle signature to the plant leaves. It showed that leaves from different plants can have their own characteristic IM values. We further investigated the infected regions of the leaves that display a relatively lower biospeckle activity than the healthy tissue. It was easy to discriminate between the infected and healthy regions of the leaf tissue. The biospeckle technique can successfully be implemented as a potential tool for the taxonomy of quality leaves. Furthermore, the technique can help boost the quality of ayurvedic medicines.